UMA PSEUDOFILÃNEA NOVA DO ESTADO DO RIO DE JANEIRO (ORTHOPTERA-TETTIGONIIDAE) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2020)
UMA PSEUDOFILÃNEA NOVA DO ESTADO DO RIO DE JANEIRO (ORTHOPTERA-TETTIGONIIDAE)